Projetos de patenteamento e a captação de financiamento venture capital - Dias, Giziane Carla (2019)
Financing transactions (TF) of startups take place in context of information asymmetry between participating agents, essentially between entrepreneurs and investors. In context of information asymmetry, patents are considered signs of quality (SQ), originated as products of patenting projects, as they can demonstrate part of a startup's technological capability. In this sense, patents become a quality signal (SQ) for evaluation and decision making by potential investors. The general objective of this research is to analyze the relationship between SQs characterized by patents and venture capital funding (VC) in startups. Previous studies and research that presented the effects of patents on VC funding in startups contributed to substantive knowledge, as they were developed with an applied approach. Such applied research approaches have resulted in descriptive and exploratory papers with reduced generalization potential. Thus, the current study was conducted from the perspective of transactional cost theory (TCT) and quality signals (SQ), aiming to offer the extension of TCT, specifically analyzing the effects of intangible assets as information asymmetry reductors, and also broadening the understanding of the characteristics of SQ, resulting in a work that seeks to allow generalizations. Regarding the methodological procedure, the quantitative approach was adopted, especially with the analysis of variance and multiple linear regression. The sample was obtained by consulting historical VC funding data on startups Series B, available in the Crunchbase database, combined with patent filing data from invested startups, available from the European Patent Office (EPO), and analysis of the websites of the patent filing companies that made up this sample. The number of patent applications has been found to be positively related to the amount of VC capital raised by startups. The findings of this paper demonstrate that intangible assets have a distinct effect from tangible assets regarding transactional cost theory, playing the role of information asymmetry reductors among agents involved in TF. As managerial contribution, we present general guidelines on how to conduct patenting projects to increase the chances of raising VC funding.